ممارسة القيادة التحويلية لدى القيادات الإدارية وأثرها على أداء العمل والعاملين بوزارة التربية والتعليم بسلطنة عمان : سمات الشخصية متغير وسيط - بلوشي، محمد سليمان خميس (Kulliyah of Education, International Islamic University Malaysia, 2021)
Leadership style is one of the important elements and fundamental pillars of the administrative work in any institution. In fact, the success or failure of any leadership style will affect the institutions' performance. In light of this and based on the Japanese theory (Z), this research examines the impact of transformational leadership practices and leaders' personality traits on the performance of the administrative staff at the Ministry of Education in Oman. It also examines the mediating role of leaders' personality traits in the relationship between transformational leadership practices and the performance of the administrative staff at the Ministry of Education in Oman. In this study, the researcher adopted the descriptive survey method, as it is an appropriate approach which suits the objectives of this study. Based on the nature of this quantitative study, the researcher used the cross-sectional method to collect its data. A questionnaire of 66 items was distributed randomly to the sample of this study (directors, head of departments and staff) from the offices of Ministry of Education in Oman. Out of the distributed questionnaires, 375 (263 males and 112 females) were returned and valid for analysis. SPSS software (version 24) was used for the preliminary descriptive analysis, while Smart-PLS software (Version 3) was employed for the main inferential analysis, namely variance-based Structure Equation Modelling (SEM). SEM via Smart-PLS was conducted in two main steps, namely the measurement model to assess the data's validity and reliability, while the structural model was conducted to examine the hypothesized relationships between the variables. The results revealed a direct impact of transformational leadership practices and leaders' personality traits on the performance of the administrative staff at the Ministry of Education in Oman. It also showed a mediating effect for the leaders' personality traits on the relationship between transformational leadership practices and the performance of the administrative staff at the Ministry of Education in Oman. The results were discussed in the light of the theoretical framework and previous studies. The study concluded with practical recommendations for Ministry of Education in Oman as well as theoretical recommendations for future studies.